CLINICAL PROFILE OF PATIENTS UNDERGOING SURGERY FOR ENDOMETRIOSIS - Dos Santos Cruz, Eliayta Cassia; Nogueira Chaves, Francisco; Ribeiro Nogueira, Lucas; Fernandes de Sousa, Mirella; Sales de Rosa, Luma (Cadernos ESP, 2025)
Objective: To delimit the clinical and epidemiological aspects of patients with endometriosis in a hospital in Ceará. Methods: Descriptive, retrospective, and cross-sectional study, analyzing data from 108 patients treated surgically. Results: The mean age was 37 years, and 68% of patients had children. Dienogest was the most commonly used medication for clinical treatment. Chronic pelvic pain was the main symptom (77%). In imaging exams, the most affected sites were the uterosacral ligaments, the retrocervical region, and the rectum. Hysterectomies were performed in 62% of cases, and intestinal surgeries in 64% of cases. The mean overall length of hospital stay was 4.2 days, with 10% of minor postoperative complications. Conclusion: The study highlights the complexity of endometriosis cases and the importance of early diagnosis and individualized treatment to improve care and the quality of life for patients.
Keywords: Endometriosis; Epidemiology; Pelvic pain; Surgery